A Study of Diffusion Phenomenon in Friction Stir Lap Welding Joints for Low Carbon Steel C10 to Aluminum Alloy AA1100-H112 - Abbass, Muna Khethier; Raheef, Kareem Mohsen (Al-Nahrain Journal for Engineering Sciences, 2018)
In this study the friction stir lap welding was carried out by a new technique (diffusion bonding phenomenon) between (AA1100 and low carbon steel C10 sheets of 3mm and 1mm thickness respectively. These alloys have difference ranges in melting temperature and other physical properties. Different parameters were used: tool rotation speeds (630, 1250) rpm, travel speeds (80, 32) mm/min. and pin length (2.8,3) mm using cylindrical threaded pin. Many tests and inspections were performed such as tensile shear test and X-Ray diffraction tests. Microhardness and microstructure observations were conducted by using optical and SEM. The above tests were used to evaluate the weld quality and joint efficiency under different welding parameters. Best result for FSLW by diffusion phenomenon appear in (low carbon steelC10 / AA1100-H112) joint at 1250rpm in 32 mm/min. with 2.8mm pin length and the maximum tensile shear strength was (3.9)KN.It was found that the highest micro hardness was (138HV) at the interface between the low carbon steel and AA1100.